2005
DOI: 10.1002/prot.20609
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of LysRS: An asymmetric state

Abstract: We report molecular dynamics simulations of the Escherichia coli Lysyl-tRNA synthetase LysU isoform carried out as a benchmark for mutant simulations in in silico protein engineering efforts. Unlike previous studies of aminoacyl-tRNA synthetases, LysU is modelled in its full dimeric form with explicit solvent. While developing a suitable simulation protocol, we observed an asymmetry that persists despite improvements to the model. This prediction has directly led to experiments that establish a functional asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…In addition, GTP was found to be a significantly poorer inhibitor of Hint-AMP formation than ATP. In support of our findings, recent modeling studies attempting to develop a molecular rationale for the substrate specificity of ecLysU have concluded that the enzyme has a greater propensity to bind ATP in the necessary productive conformation than GTP (44).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, GTP was found to be a significantly poorer inhibitor of Hint-AMP formation than ATP. In support of our findings, recent modeling studies attempting to develop a molecular rationale for the substrate specificity of ecLysU have concluded that the enzyme has a greater propensity to bind ATP in the necessary productive conformation than GTP (44).…”
Section: Discussionsupporting
confidence: 85%
“…A number of oligomeric aaRS have previously been shown to exhibit activity of half of the sites despite containing multiple, seemingly chemically equivalent active and tRNA-binding sites (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30). The mode of tRNA binding described herein argues that SepSecS may follow the sequential model of allosteric regulation (49).…”
Section: Discussionmentioning
confidence: 83%
“…The TyrRS dimer binds one tRNA Tyr (15) and catalyzes formation of 1 mol of tyrosyl adenylate (16 -20), and tetrameric PheRS (15,21) and SepRS (22) employ two of their four catalytic and tRNA-binding sites at a time. Likewise, class II enzymes, bacterial LysRS-II (23,24), AspRS (25), and HisRS (26) and the archaeal and eukaryotic ProRS (27,28) behave according to the "half of the sites" model. The situation is less clear in the case of PylRS and SerRS.…”
mentioning
confidence: 99%
“…In site 2, R269 appears to act as a lid to close the binding pocket; in site 1, this lid has been displaced leaving the pocket open. Other active site/first shell amino acid residues of potential importance to Ap 4 A/Ap 3 A formation can be seen by inspection of the molecular dynamics simulation and X‐ray crystal structures of LysU with bound substrates (Fig. A).…”
Section: Introductionmentioning
confidence: 99%
“…LysU is homodimeric with one active site associated with each monomeric polypeptide. Previous order-of-addition experiments [16,17] show that LysU is initially loaded at each site with Mg 2+ and L-lysine, giving a LysU:6Mg 2+ : L-lysine 2 intermediate state with significant conformational distortion. Thereafter, ATP binds to a single active site (designated 2) developing a structural asymmetry culminating in distortions in the motif 2 loop at site 1.…”
Section: Introductionmentioning
confidence: 99%